1987
DOI: 10.1099/00221287-133-8-2079
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Inhibition of Sporulation of Bacillus subtilis Caused by Increasing the Number of Copies of the spO0F Gene

Abstract: The Bacillus subtilis spoOF gene was cloned on a 6.3 kbp BgnI fragment. The effect on sporulation of amplification of the SPOOF region was examined. Sporulation was inhibited to less than 5 % of that of the parental strain when as few as four copies of the spoOF region were present. Subclones, constructed in autonomous or integrative vectors, were used to demonstrate that the region responsible for the copy-num ber-dependent asporogeny corresponded closely with the s p d F structural gene. A possible mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…However, this result contradicts previous in vivo studies, which indicate that 0F overexpression inhibits sporulation (Chapman and Piggot, 1987; Chastanet et al, 2010; Sen et al, 2011). To resolve this discrepancy, we made a change to the conventionally assumed phosphorelay architecture (Figure 2A without red arrow) and incorporated substrate inhibition of KinA by 0F into the phosphorelay model (red arrow, Figure 2A).…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…However, this result contradicts previous in vivo studies, which indicate that 0F overexpression inhibits sporulation (Chapman and Piggot, 1987; Chastanet et al, 2010; Sen et al, 2011). To resolve this discrepancy, we made a change to the conventionally assumed phosphorelay architecture (Figure 2A without red arrow) and incorporated substrate inhibition of KinA by 0F into the phosphorelay model (red arrow, Figure 2A).…”
Section: Resultscontrasting
confidence: 96%
“…This substrate inhibition effect has been demonstrated previously (Grimshaw et al, 1998), but has received little attention in mathematical modeling studies. This effect is however essential for explaining the inhibitory effect of 0F overexpression on sporulation (Chapman and Piggot, 1987; Chastanet et al, 2010; Sen et al, 2011). Our results demonstrate that this negative feedback based on the substrate inhibition of KinA by 0F plays a critical role in coupling 0A~P pulsing to DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as discussed in the model below, there is an additional post-translational “bandpass” regulatory effect due to the dual role of Spo0F, which is required for Spo0A phosphorylation but can also lead to Spo0A dephosphorylation, due to reverse phosphotransfer and the activity of Spo0F phosphatases. These effects can cause net phosphorylation of Spo0A to first increase, and then decrease, as Spo0F levels rise [19]. Third, gene expression during progress to sporulation occurs in a pulse-like fashion every cell cycle [7], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hashiguchi et al (1986) showed that amplification of the tmrA locus resulted in tunicamycin resistance and hyperproduction of a-amylase. Piggot and colleagues also reported the amplification of an integrated plasmid within chromosome (Chapman & Piggot, 1987;Piggot & Curtis, 1987). Wilson & Morgan (1985) demonstrated that gene amplification correlates with the occurrence of tetracycline (Tc) resistance.…”
Section: Introductionmentioning
confidence: 99%